Evaluation of tyrosine kinase receptors in brain metastases of clear cell renal cell carcinoma reveals cMet as a negative prognostic factor. Issue 6 (7th June 2015) - Schiefer, Ana‐Iris; Mesteri, Ildiko; Berghoff, Anna S; Haitel, Andrea; Schmidinger, Manuela; Preusser, Matthias; Birner, Peter
Abstract : Aims: Brain metastases (BMs) of clear cell renal cell carcinoma (ccRCC) are associated with a dismal prognosis, with limited treatment options. Tyrosine kinases are relevant 'druggable' biomarkers. The aim of this study was to evaluate the tyrosine kinase receptors anaplastic lymphoma kinase (ALK), epidermal growth factor receptor (EGFR), platelet‐derived growth factor receptor‐α (PDGFRA) and cMet in a large series of ccRCC BMs. Methods and results: ALK, EGFR, PDGFRA and cMet protein expression was determined by immunohistochemistry in 53 ccRCCs BMs and 12 matched primary tumours. ALK and MET gene status and copy number alterations of chromosome 7 were studied with fluorescence in‐situ hybridization (FISH). Data on the expression of hypoxia‐inducible factor 1α (HIF1α) and Ki67 and microvessel density were available from previous studies. ALK was negative in all analysed specimens. EGFR was overexpressed in 41 of 51 (80.4%) BMs and in seven of eight primary tumours, PDGFRA was overexpressed in all BMs except one and in all primary tumours, and cMet was expressed in 26 of 50 (52%) BMs and in two of seven primary tumours, and did not correlate with MET amplification or polysomy 7. cMet was the only parameter associated with significantly shorter BM‐specific survival (median 8 months versus 33 months, P  = 0.005, Cox regression). Conclusions: EGFR, PDGFRA and cMet are commonly overexpressed in ccRCC BMs. cMet overexpression correlates with significantly shorter BM‐specific survival.